Efficacy, Safety, and Tolerability of Nasal Wash in Patients with Upper Respiratory Tract Diseases - La Mantia, Ignazio; Stilo, Giovanna; Lentini, Lepanto; Ciprandi, Giorgio (International Archives of Otorhinolaryngology, 2025)
Nasal irrigation is a standard therapeutic option to clean the upper airways to remove abundant secretions and harmful substances. The Nasal Wash (SIIT, Milan, Italy) sinus irrigation system contains saline, bicarbonates, and polyethylene glycol.The present randomized controlled trial evaluated and compared the Nasal Wash hypertonic solution (NW-HS) with physiological saline (PS) in patients with nasal symptoms common to different upper airway diseases (infectious rhinitis, allergic rhinitis, and acute and chronic rhinosinusitis).The symptomatic patients were divided into two groups: those receiving NW-HS 1 to 2 times a day for 7 days and those receiving PS 1 to 2 times a day for 7 days. The primary efficacy measures included total nasal symptom score (TNSS) and the score on the verbal numeric rating scale (VNRS), assessed at baseline and during the treatment period.In total, 70 patients participated in the trial: 35 were allocated to the NW-HS group and 35 to the PS group. In the NW-HS group, we observed a significant reduction in the TNSS over time, at rates higher than those of the PS group (p < 0.001), as well as a significant reduction in the VNRS score at all observation times, and also at rates higher than those of the PS group (p < 0.001). The safety was good for all patients.The present trial documented the efficacy and safety of NW-HS in the treatment of nasal symptoms common to upper respiratory tract disorders. Most of the beneficial effects appeared as early as three days after the beginning of the treatment. In addition, compared to PS, NW-HS showed impressive results; thus, it may represent a safe and valuable option in the non-pharmacological therapy for rhinitis.
Keywords: upper respiratory tract diseases; nasal irrigation; saline solution; bicarbonates; PEG